- Raynaud’s phenomenon - Goller, Wolfgang G.; Mazza, Milton; Burstin, Jacobo; Nozar, José V.; Fernández Perdomo, Gonzalo; Torterolo, Edgardo; Portos, Ruben (Cirugía del Uruguay, 1982)
Raynaud's Phenomenon , is an acral suffering with certains simptom as palling and coolng of the fingers with pain nd sometime trophic disturbance. In most of the cases it's due to other disease (Raynaud's syndrome ), finding i t less recuen tly independen t (Raynaud 's disease). The authors analized the steps for establishing the ethiological and diferencial dianosis and state the therapeutic possibilities. In the Raynaud syndrome success is brought out by intra- arterial herapy as an initiaJ treatment leaving the dorsal sympathectomy for a later procedure wich goes first for Raynaud's disease herapy;